Men, ideas and politics - Drucker, Peter F. [ (Peter Ferdinand)] , 1909-2005 (The Drucker library, 2010)
"The Political Issues Impacting Our global economy have changed drastically over the last few decades, but some things have not changed---the relationship between business and politics remains a potent driver of world events." "Even with the modern crises of global terrorism, the international monetary threat posed by corporate greed, "bubble" economics, and a host of other shifts in global economic and political realities, Peter Drucker's Men, Ideas, and Politics remains as timely as ever for its presentation and contextualization of the challenges facing modern leadership. This collection of thirteen essays, originally released in 1971, serves as a reminder that although circumstances may present the world with challenges as new as each generation, the history of how those challenges were met remains our greatest teacher." "Drucker examines paradigm shifts in presidential politics while arguing that there is a "secret art" to the presidency. His history of game-changing mergers and acquisitions provides a useful primer for understanding the impact of corporate consolidation on the world economy. Other pieces offer unparalleled insights into the financial upheaval following Wall Street's and the banking industry's near-collapses over the past twenty years." "Four decades later, Drucker's work stands not just as a learned consideration of historical political, economic, and cultural thought, but as a revealing lens through which to view our modern world. It is a must-read for business leaders---today's or tomorrow's."--BOOK JACKET